The colonial grid: mapping the social work classroom. Issue 2 (3rd July 2022) - Carranza, Mirna
ABSTRACT: Social work education in the Global North is rooted in an underlying discourse of power that defines the 'knower' parameters and, therefore, legitimises who can 'teach'. For this paper, the spatial orientation of whiteness in the classroom in a time of coloniality and intersectionality is the unit of analysis. This whiteness is made visible by not just the presence of the racialised 'Other, ' but a non-white, female professor from the Global South educating from marginalised and discounted knowledge. Using reflexivity and story-telling methods combined with critical theory, I present an analysis of my lived experience of navigating social work students and institutions' whiteness. How the classroom is experienced becomes a part of racialised professors' lived process, embodying the tensions and contradictions in the profession and knowledge base. Using this analysis, I map out the colonial grid embedded in the social work classroom.